Adipose‐Derived Exosomes Exert Proatherogenic Effects by Regulating Macrophage Foam Cell Formation and Polarization. Issue 5 (3rd March 2018) - Xie, Zulong; Wang, Xuedong; Liu, Xinxin; Du, Huaan; Sun, Changbin; Shao, Xin; Tian, Jiangtian; Gu, Xia; Wang, Hailong; Tian, Jinwei; Yu, Bo
Abstract : Background: Obesity is causally associated with atherosclerosis, and adipose tissue (AT)–derived exosomes may be implicated in the metabolic complications of obesity. However, the precise role of AT‐exosomes in atherogenesis remains unclear. We herein aimed to assess the effect of AT‐exosomes on macrophage foam cell formation and polarization and subsequent atherosclerosis development. Methods and Results: Four types of exosomes isolated from the supernatants of ex vivo subcutaneous AT and visceral AT (VAT) explants that were derived from wild‐type mice and high‐fat diet (HFD)–induced obese mice were effectively taken up by RAW264.7 macrophages. Both treatment with wild‐type VAT exosomes and HFD‐VAT exosomes, but not subcutaneous AT exosomes, markedly facilitated macrophage foam cell generation through the downregulation of ATP‐binding cassette transporter (ABCA1 and ABCG1)–mediated cholesterol efflux. Decreased expression of liver X receptor‐α was also observed. Among the 4 types of exosomes, only HFD‐VAT exosomes significantly induced M1 phenotype transition and proinflammatory cytokine (tumor necrosis factor α and interleukin 6) secretion in RAW264.7 macrophages, which was accompanied by increased phosphorylation of NF‐κB‐p65 but not the cellular expression of NF‐κB‐p65 or IκB‐α. Furthermore, systematic intravenous injection of HFD‐VAT exosomes profoundly exacerbated atherosclerosis in hyperlipidemic apolipoprotein E–deficient mice, as indicated by the M1 marker (CD16/32 and inducible nitric oxide synthase)–positive areas and the Oil Red O/Sudan IV–stained area, without affecting the plasma lipid profile and body weight. Conclusions: This study demonstrated a proatherosclerotic role for HFD‐VAT exosomes, which is exerted by regulating macrophage foam cell formation and polarization, indicating a novel link between AT and atherosclerosis in the context of obesity.